Adubação fosfatada para o arroz irrigado em solos com diferentes capacidades de adsorção de fósforo - Cardoso, Eduardo Flores (2007)
In irrigated rice crop, the lowland soils can supply the plants with different phosphorus quantities due to the source material and phenomena that occur in the different oxidation and reduction cycles of these soils. An important soil factor that regulates the phosphorus availability for the plants is the maximum phosphorus adsorption capacity. Therefore, the objectives of this work were to evaluate the response of the irrigated rice fertilized with two sources of phosphorus in lowland soils with different phosphorus adsorption capacity and to evaluate the prediction capacity of the methods Mehlich-1 and Ionic Exchange Resin in Sphere regarding the phosphorus availability for the irrigated rice in these soils. The soil samples were taken from the top 20 cm of three lowland soils with different maximum phosphorus adsorption capacity (MPAC): Typic Albaqualf, low MPAC; Vertic Albaqualf, average MPAC and Typic Endoaqualf, high MPAC. The experimental units were constituted of plastic buckets containing 6 kg of dry soil, where two phosphorus sources (phosphate rock and triple superphosphate) and six levels of phosphorus: 0, 10, 20, 40, 80, 160 mg kg-1 P were applied, with three replications, totaling 128 experimental units. The pots were positioned in the greenhouse in a completely randomized experimental design. The rice was cultivated for 45 days and the dry matter weight was quantified through aerial part of the plants. The phosphorus content was analyzed by extractor Mehlich-1 and Resin methods in the soil, in the soil solution and in the plant. The obtained results showed that: Typic Albaqualf respond with increased dry matter weight of rice plant aerial part up to the level of 10 mg kg-1 of phosphorus applied in the soil, while in the Typic Endoaqualf the response to the applied phosphorus was up to the level of 80 mg kg-1. Vertic Albaqualf did not respond to phosphorus; soil with higher maximum phosphorus adsorption capacity (MPAC), Typic Endoaqualf, required higher phosphorus quantity (phosphate rock and triple superphosphate) to reach maximum dry matter weight of rice plant aerial part up; the triple superphosphate presented greater solubility than phosphate rock Daoui during the flood of the lowland soils in this experiment; the extractor Mehlich-1 and the Ion Exchange Resin method were equivalent in the prediction capacity of the phosphorus availability for the irrigated rice in the lowland soils in this experiment.